Exploring virtual reality mechanics in puzzle design - Nyyssönen Taneli; Smed Jouni (Springer, 2022)
We explore practical implementations of various custom virtual reality mechanics, developed specifically for this study, in the context of puzzle game design with an experimental approach. These mechanics include swimming, crawling, climbing, and hiding objects in virtual spaces. Each mechanic has two different variations: realistic and game-like, and the main goal is to test which variation is more enjoyable to use.
Convenience sampling is used in the study and the sample size is 22 volunteers. Both qualitative and quantitative data are collected. The data collection methods used are questionnaire and observation. The enjoyability of the mechanics is evaluated based on four different aspects: perceived realism, personal traits and abilities of the testing sample, the testing order, and perceived difficulty. A special interest is to observe whether real-life skills corresponding to the studied mechanics affect the enjoyment and performance levels in the respective mechanics.
The more realistic mechanics turn out to be more enjoyable by a significant margin, suggesting that they should be utilised in the future. Additionally, the real-life diving and swimming skills, puzzle variation testing order, previous gaming experience, and testers' familiarity with the testing supervisor are identified to have a clear impact on the enjoyment levels.